Musculoskeletal and esthetic complications after neonatal thoracotomy: Revisited - Gali Divya; Vijay Kumar Kundal; Pinaki Ranjan Debnath; Raja Sekhar Addagatla; Anil Kumar Garbhapu; Arnab Kumar Saha; Atul Kumar Meena; Shalu Shah; Amita Sen (Wolters Kluwer Medknow Publications, 2022)
Aim: The aim is to study the complications of neonatal thoracotomy and its preventive measures. Methods: We retrospectively reviewed 53 neonates who underwent thoracotomy from January 2017 to December 2019 for a period of 3 years. Patient demographic data, primary disease for which they underwent thoracotomy, postoperative complications (immediate and delayed) during follow-up were documented. Results: During 3-year period, 53 neonates underwent thoracotomy for various surgical pathologies. The indications were esophageal atresia with tracheoesophageal fistula (n = 49), eventration of diaphragm (n = 3), congenital lobar emphysema of left upper lobe of lung (n = 1). Most of them were right posterolateral thoracotomies (n = 48, 90.56%) and left posterolateral thoracotomy was done in only 5 cases (9.43%). Associated anomalies were seen in 22 cases, such as cardiac (n = 19), renal (n = 4) and gastrointestinal (n = 5). Associated comorbidities seen in 14 cases; preterm (n = 4), low birth weight (n = 13), delayed presentation (n = 6). Early postoperative complications such as pneumonia (34%, n = 18) and wound infection (11.3%, n = 6) were noted. Delayed complications include musculoskeletal abnormalities (n = 19, 35.8%) and esthetic complications such as asymmetry of chest (5.6%). Conclusion: Neonatal thoracotomy is associated with complications such as pneumonia, wound infections, and musculoskeletal abnormalities such as asymmetry of chest and scoliosis. These can be prevented by adequate postoperative pain relief, muscle-sparing thoracotomies, avoiding tight closures, and nerve injuries. Long-term follow-up is required because these complications may manifest later on also. Early detection and institution of physiotherapy may help.